How MOOCs Are Perceived by Moroccan Students and Teachers? - Razouki, Abdelaziz; Khzami, Salah-eddine; El Khatabi, Ikbal; Agorram, Boujemaa; Selmaoui, Sabah (European Scientific Journal, ESJ, 2017)
The Moroccan university is increasingly experiencing a strong growth in the numbers of students. This process of massification alters the quality of learning, especially in open-access institutions where human resources and the capacity to host are increasingly limited. To improve the quality of learning, which first involves improving the quality of teaching within the University, Cadi Ayyad University in Marrakech (UCAM) launched a platform of MOOCs (Massive Online Open Courses) in 2013. In this article, we question the opening of the Moroccan university on this technology. Our study is anchored in the context of the Cadi Ayyad University of Marrakech. We are particularly interested in the following question: what are the perceptions of students and teachers about this device? Do they feel that using MOOCs “changes something”? Our methodological approach describes all the stages of data collection and processing including the content analysis model. We distributed a questionnaire to a group of students and conducted semi-structured interviews with teachers. The questionnaires collected and the interviews made it possible for answers to be provided to the questions asked. The most salient results show that the students as well as the teachers who participated in our study appreciate the use of MOOCs as a support to the face-to-face class. However, this technology has disadvantages including lack of exchanges with teachers and between students. Ongoing product improvements were called for, including the design in association with MOOC of student activities, assessments and discussion forums, and on the other hand, recording the videos in the presence of the students